Exploration and Profiling of Bacteria Symbionts in Arothron stellatus from the Thoothukudi Coast - Kanthimathi, P.; Joslin, P. J. (Asian Journal of Biological and Life Sciences)
Marine organisms inhabit a distinct ecological niche compared to terrestrial counterparts, leading to significant variations in their secondary metabolite profiles. Symbiotic relationships between microorganisms and marine organisms are prevalent and diverse in the marine environment. In this study, pufferfish Arothron stellatus specimens were collected from the Thoothukudi coast and their associated liver bacteria were examined. Two symbiotic strains were isolated and characterized through cultural, morphological and molecular analyses. These isolates exhibited traits such as motility, rod-shaped morphology and both Gram-positive and Gram-negative features. Based on 16S rRNA gene analysis, the strains were identified as Achromobacter xylosoxidans (L1) and Bacillus cereus (L2). The respective sequences have been deposited in the Genebank under accession numbers OP420554 (L1) and OP42055 (L2). Tetrodotoxin (TTX) is a well-known toxin present in puffer fishes, and it is produced by various bacterial species associated with these fish. Our findings suggest that the isolated bacterial strains, Achromobacter xylosoxidans (L1) and Bacillus cereus (L2), may potentially contribute to TTX production. Further research is warranted to elucidate the synthesis mechanism of TTX and the role of bacteria in this process.
Keywords: 16S rRNA.; Achromobacter xylosoxidans; Arothron stellatus; Bacillus cereus; GeneBank